1998
DOI: 10.1103/physrevlett.81.3765
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Superconductivity ofSr2RuO4to 3 K by Embedded Metallic Microdomains

Abstract: We have found that the quasi-two-dimensional superconductor Sr 2 RuO 4 with the intrinsic transition temperature T c 1.5 K exhibits a remarkable enhancement in T c up to 3 K, if lamellar microdomains of ruthenium metal are embedded. Measurements of the anisotropy in the upper critical fields indicate that the 3-K superconductivity is sustained essentially in the layered structure of Sr 2 RuO 4 . We suggest that the enhanced interlayer coherence provided via metallic Ru plays a key role in the doubling of T c .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
122
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 19 publications
7
122
2
Order By: Relevance
“…The Ginzburg-Landau equations then read 17,28 . A bulk crystal from this batch was measured and showed a broad transition with a bulk T c around 1.35 K, slightly lower than the optimal T c for Sr 2 RuO 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ginzburg-Landau equations then read 17,28 . A bulk crystal from this batch was measured and showed a broad transition with a bulk T c around 1.35 K, slightly lower than the optimal T c for Sr 2 RuO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…17), may provide insight into the mechanism issue. The T c enhancement was attributed to the capillary effect at the Ru/Sr 2 RuO 4 interface 18 .…”
mentioning
confidence: 99%
“…It is reported that Sr 2 RuO 4 has exotic property called as 3K phase [17] when Ru metal is embedded in the single crystal. We speculate that the enhancement of T c is due to the increase of the anisotropy (i.e., decrease of α) near the interface region between Sr 2 RuO 4 and Ru metal.…”
mentioning
confidence: 99%
“…20,21 On the basis of ultrasonic experiments and the Ehrenfest relation, T c is predicted to also be suppressed by the in-plane UAP along the [100] direction P [100] at a rate of (1/T c )(dT c /dP [100] ) = −(0.85 ± 0.05) GPa −1 . 22,23 In contrast, the enhancement of T c up to about 3 K is observed in Sr 2 RuO 4 -Ru eutectic crystals, 24 in which superconductivity with higher T c probably occurs in the Sr 2 RuO 4 part around Sr 2 RuO 4 -Ru interfaces as a consequence of the strong lattice distortion due to lattice mismatch. [24][25][26] A similar enhancement of T c can be caused by out-of-plane UAP P [001] in non eutectic Sr 2 RuO 4 .…”
Section: Introductionmentioning
confidence: 98%
“…22,23 In contrast, the enhancement of T c up to about 3 K is observed in Sr 2 RuO 4 -Ru eutectic crystals, 24 in which superconductivity with higher T c probably occurs in the Sr 2 RuO 4 part around Sr 2 RuO 4 -Ru interfaces as a consequence of the strong lattice distortion due to lattice mismatch. [24][25][26] A similar enhancement of T c can be caused by out-of-plane UAP P [001] in non eutectic Sr 2 RuO 4 . 27 However, because of the technical difficulties in directly measuring the effects of in-plane UAP and uniaxial strain, the effect of in-plane UAP on Sr 2 RuO 4 has been under discussion 28,29 and the effect of in-plane uniaxial strain on Sr 2 RuO 4 has been reported only recently.…”
Section: Introductionmentioning
confidence: 98%